The combined effect of sprint interval training and postexercise blood flow restriction on critical power, capillary growth, and mitochondrial proteins in trained cyclists - Mitchell, E. A.; Martin, N. R.; Turner, M. C.; Taylor, C. W.; Ferguson, R. A. (Journal of Applied Physiology, 2019)
Sprint interval training (SIT) combined with postexercise blood flow restriction (BFR) is a novel method to increase maximal oxygen uptake (VO2max) in trained individuals and also provides a potent acute stimulus for angiogenesis and mitochondrial biogenesis. The efficacy to enhance endurance performance, however, has yet to be demonstrated. Trained male cyclists (n = 21) (Vo2max: 62.8 ± 3.7 ml·min-1·kg-1) undertook 4 wk of SIT (repeated 30-s maximal sprints) either alone (CON; n = 10) or with postexercise BFR (n = 11). Before and after training V o2max, critical power (CP) and curvature constant (W') were determined and muscle biopsies obtained for determination of skeletal muscle capillarity and mitochondrial protein content. CP increased (P = 0.001) by a similar extent following CON (287 ± 39 W to 297 ± 43 W) and BFR (296 ± 40 W to 306 ± 36 W). Vo2max increased following BFR by 5.9% (P = 0.02) but was unchanged after CON (P = 0.56). All markers of skeletal muscle capillarity and mitochondrial protein content were unchanged following either training intervention. In conclusion, 4 wk of SIT increased CP; however, this was not enhanced further with BFR. SIT was not sufficient to elicit changes in skeletal muscle capillarity and mitochondrial protein content with or without BFR. However, we further demonstrate the potency of combining BFR with SIT to enhance Vo2max in trained individuals. NEW & NOTEWORTHY This investigation has demonstrated that 4 wk of sprint interval training (SIT) increased critical power in trained individuals; however, postexercise blood flow restriction (BFR) did not enhance this further. SIT, with or without BFR, did not induce any changes in skeletal muscle capillarity or mitochondrial protein content in our trained population. We do, however, confirm previous findings that SIT combined with BFR is a potent stimulus to enhance maximal oxygen uptake.